Factors associated with non-participation in a health screening programme and its barriers: findings from the community empowers the nation programme (KOSPEN), Malaysia 2016 - Lim, Kuang Kuay; Hasimah Ismail,; Nur Liana Ab Majid,; Thamil Arasu Saminathan,; Rosnah Ramly,; Chan, Ying Ying; Tahir Aris, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction The Ministry of Health, Malaysia had introduced the community based action programme (KOSPEN) to improve the early detection of non-communicable diseases (NCDs) in the population. This study aims to identify factors associated with non-participation in screening activities and its barriers. Methods This cross sectional study was conducted from May to June 2016 in KOSPEN localities. A total of 2354 adults aged 18 years and above were selected using a two-stage stratified cluster sampling design. The data were obtained through face-to-face interviews using validated questionnaires. Multiple logistic regression analysis was used to determine the sociodemographic factors associated with non-participation in health screening. Results Out of 2156 respondents interviewed (response rate of 91.6%), approximately 75% (n=1624) of the respondents did not participate in the KOSPEN health screening programme. Multivariable logistic regression analyses revealed that, males (aOR: 2.35, 95% CI 1.21, 4.55) and those working in private sector (aOR: 2.11, 95% CI 1.21, 3.67) were more likely to not participate in health screening. While, age, ethnicity, level of education, marital status and household income were not significantly associated with non-participation in health screening. The barrier for not participated were “did not know health screening was conducted in their localities” (39.3%) and had no time to attend the programme (18.2%). Conclusions The study findings are of public health concern as about three quarters of the respondents failed to participate in this programme because they didn’t know that there were health screening activities conducted in their localities beside the time constraint problems. Thus, KOSPEN health screening activities should be made known to the community especially males who are mostly working in the private sector.